Monetary policy transmission below zero - Zuzana Fungáécová; Eeva Kerola; Olli-Matti Laine (Bank of Finland, 2023)
This study considers the pass-through of different ECB monetary policy measures to bank corporate lending rates of different maturities during 2010-2020. We find changes in the pass-through as policy rates first dip below zero in 2014 and again when negative interest rates become more persistent during the "low-for-long" period beginning in 2016. Overall, the transmission of monetary policy to bank lending rates appears to have become less efficient below zero, particularly in the case of corporate loans with short maturities. The effect is most pronounced for banks that did not lower their own retail deposit rates below zero or held significant amounts of negative interest-bearing central bank deposits. We see a reversal in the pass-through during the low-for-long period with banks raising their lending rates as monetary policy is eased. Unconventional monetary policy measures such as targeted longer-term refinancing operations (TLTROs) and quantitative easing (QE) appear to have mitigated these contractionary effects, even during the low-for-long period. In our examination of below-zero policy tools, we provide evidence that negative policy rates and TLTROs complement each other, while negative policy rates and QE do not.
Keywords: E52; E58; G21; 330; negative interest rates; unconventional monetary policy; lending rates; bank lending channel; euro area